(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of treatment adherence of hypertensive patients at the Cardiology Clinic, Bai Chay Quang Ninh Hospital in 2024 and some related factors. Method: Cross-sectional descriptive study with analysis. Results: The rate of compliance with hypertension treatment of the study subjects from the average level or higher is 55,0%, the poor level is 45,0%. The results of the analysis to find the relationship show that factors such as: Diet, smoking, drinking alcohol, home monitoring of hypertension, periodic re-examination, duration of illness and complications are related to treatment adherence with p<0,05. At the same time, the factors of compliance with not using alcohol, not smoking and physical exercise are also related to good blood pressure control with p<0,05. Conclusion: The rate of compliance with hypertension treatment of the study subjects from the average level or higher is 55,0%; Lifestyle factors that are associated with treatment adherence with statistical significance p<0,05 include: Diet, smoking, alcohol consumption, home monitoring of hypertension, periodic re-examination, duration of illness and complications; in addition, adherence to no drinking alcohol, no smoking and physical exercise are also associated with good blood pressure control with p<0,05. Other factors such as gender, age, occupation, education level and living area... have not been found to be associated with treatment adherence in hypertensive patients (with p>0,05).